Harnessing l-arabinose isomerase for biological production of d-tagatose: Recent advances and its applications. (January 2021) - Ravikumar, Yuvaraj; Ponpandian, Lakshmi Narayanan; Zhang, Guoyan; Yun, Junhua; Qi, Xianghui
Abstract: Background: d -tagatose is regarded as one of the most valuable rare sugars in the current market and its biotechnological ways of production is a very hot topic as of today. As a ketohexose, d -tagatose having low-caloric value and 90% of sweetness with sucrose is a rare monosaccharide that exists extremely in low quantities in nature. Owing to distinct properties and beneficial functions on human health it has received a great interest and attained Generally Recognised as Safe (GRAS) status by the U.S. Food and Drug Administration (USFDA) in 2010. Scope and approach: Due to scarcity in nature, production of d -tagatose either by chemical or biological methods is of utmost importance. In order to overcome the challenges that occur in chemical production, recently, biological process by using l -arabinose isomerase (L -AIs) for converting d -galactose to d -tagatose has allured researchers to find out more new ways to synthesize it in a cheap and eco-friendly manner. Herein, a brief summary on the scope of enzyme engineering methods like rational, semi-rational and directed evolution approaches to generate tailored L -AIs for improving d -tagatose yield and its function under harsh conditions are summarized. In addition, comparison of biochemical parameters and structural key aspects are also highlighted in this paper. Key findings and conclusions: Till date, L -AIs from various microbial sources are identified and characterized. Elucidating crystal structures and catalytic mechanism has elevated the researcher's interest to modify the L -AIs at molecular level and demonstrate its potential that is suited for industrial settings. However, works to produce d -tagatose from cheap renewable feedstocks and methods like immobilization and cell-surface display of L -AIs for efficient uptake and biotransformation of d -galactose are scarcely reported. In future, by employing the aforementioned strategies, the research studies must be focused more on shaping L -AIs as powerful biocatalysts to produce d -tagatose at industrial scale that necessitates for the human welfare. Highlights: Scope and importance of l -arabinose isomerase (L -AI) for biological production of d -tagatose is reviewed. Engineering L -AI by various protein engineering methods is comprehensively discussed. Feasibility of using renewable sources and industrial by-products wastes for d -tagatose synthesis are highlighted. Importance of immobilization and other cellular engineering for enhancing d -tagatose yield or efficient substrate utilization are discussed. Use of unnatural amino acid mutagenesis and downstream processing research needs are highlighted in future research area.